Rules versus discretion: Empirical evidence from Indonesia's intergovernmental transfer system - Gerrit J. Gonschorek (University of Freiburg, Department of International Economic Policy (iep), 2021)
Can formula-based transfers effectively limit favoritism and political patronage in public funds allocations? Formula-based transfers that tie the allocation of public funds to local development indicators are often seen as one effective measure to reduce special-interest politics, although the limited empirical evidence on formula-based transfers suggests the opposite. However, the few existing empirical studies evaluate formula-based transfers without comparing them to a more discretionary counterfactual, such as a non-formula-based institutional transfer design. Indonesia's institutional public grant design provides a unique opportunity to compare these two transfer designs within the same country for the first time. My analysis allows me to investigate special interests in public funds allocations holding the political system, the observation period, and the government officials involved constant, while varying the institutional transfer design. Using a fixed-effects model on an unbalanced panel data set of 428 Indonesian districts from 2004- 2017, the results show that non-formula-based special allocation grants are systematically biased toward Indonesia's national Budget Commission members' home districts. The home districts of the same set of Budget Commission members do not, in contrast, receive significantly higher per capita transfers under the formula-based transfer design. These results illustrate that - in contrast to its more discretionary alternative - a formula-based institutional public grant design can effectively limit public fund manipulations by government officials.
Keywords: 330; Regelbindung versus Diskretion; Finanzausgleich; Entwicklungsindikator; Indonesien